Prawne aspekty emisji obligacji przez jednostki samorządu terytorialnego - Zawadzka, Patrycja (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The paper presents the issuance of bonds as a form of capital raising and the procedure for issuance of bonds by units of local self-government. It presents institutional and legal conditions of the Polish capital market.Units of local self-government have been issuing municipal bonds on an increasing scale in recent years. The funds raised on the capital market are an alternative to bank loans which are the source of financing of the budget deficit and government investments. Units of local self government invest in roads, education, environmental protection, purchase of vehicles for public transport. The purpose of this article is also to analyze the legal regulations related to the issue of bonds on the regulated market.
Keywords: jednostki samorządu terytorialnego; emisja obligacji; prawne aspekty